Analysis of the structure and function of microbial community in late-stage of grass carp (Ctenopharyngodon idella) farming ponds - Shuhui Niu; Kai Zhang; Zhifei Li; Jun Xie; Guangjun Wang; Hongyan Li; Ermeng Yu; Yun Xia; Jingjing Tian; Wangbao Gong (Aquaculture Reports, 2023)
Microbial communities in aquaculture ponds play a critical role in pond productivity and the success of fish production. Nevertheless, our current understanding of the functional diversity of bacterial microbiomes in grass carp pond water and sediments is fragmentary. This study utilized high-throughput sequencing technology and community level physiological profiling (CLPP) methods to investigate microbial communities and metabolic activity of bacterial found in water samples and sediments from eight typical grass carp (Ctenopharyngodon idella) culturing pond in southern China. The correlations between putative function using PICRUSt2 and actual metabolic profiles via Biolog EcoPlates was assessed. Carbohydrates (32.51 %), amino acids (23.13 %), and polymers (16.61 %) were the most dominant carbon sources utilized by the microbial community in the sediment; while carbohydrates (34.72 %), amino acids (25.49 %), and polymers (16.15 %) were also utilized most often in the water samples. In the sediment samples, Proteobacteria (24.67 %), Chloroflexi (15.30 %), and Firmicutes (13.74 %) were the most dominant bacteria phyla. Actinobacteriota (32.62 %), Cyanobacteria (25.06 %), and Proteobacteria (17.51 %) were the most dominant bacteria phyla in the water samples. Moreover, our results suggested that the nitrogen transformations bacterial genera (Bacillus, Bradyrhizobium, Brocadia, Halomonas, and Vogesella) were positively correlated with carbon source utilization of the microbial community in the Biolog EcoPlates in the sediment. Dechloromonas and Pseudomonas were significantly negatively correlated in the water samples. In addition, there was a significant correlation between predicted function and the actual metabolic characteristics of microbial communities in sediment and water samples. The results facilitate detailed perspective of the relationship between the microbial community structure and the function in grass carp ponds and also provide a reference for the selection of suitable carbon sources in aquaculture wastewater treatment technology.